Bandwidth enhancement of a monopole exciter by using a chip-inductor-loaded shorted strip. Issue 11 (23rd July 2016) - Chen, Shu-Chuan; Tsou, Yu-Chuan
ABSTRACT: This paper presents an internal uniplanar monopole exciter fabricated on a 0.8-mm thick FR4 substrate. It can be arranged in the hinge slot of a laptop computer for a long-term evolution/wireless wide area network operation in the 698–960 and 1710–2690 MHz bands. The monopole exciter, which comprises feeding and chip-inductor-loaded shorted strips, occupies a compact area of 25 × 8 mm with a volume of only 0.2 cm 3 . The exciter antenna not only integrates with the metal covers, but also excites several resonant modes of the hinge slot. The chip-inductor-loaded shorted strip is employed for exciting the hinge slot to enhance lower band bandwidths. The proposed monopole exciter antenna not only serves as an exciter, but also serves as a radiator for generating several of its resonant modes. It can be installed in the hinge slot and has wide operating bands with high radiation efficiency. Over the lower and upper bands, the antenna efficiencies are higher than 56%, which is favorable for practical applications.